Development, evaluation, and overview of standardized training phantoms for abdominal ultrasound-guided interventions - Seitzinger, Max; Gnatzy, Franziska; Kern, Sabine; Steinhausen, Ralf; Klammer, Jana; Schlosser, Tobias; Blank, Valentin; Karlas, Thomas (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Ultrasound (US) represents the primary approach for abdominal diagnosis and is regularly used to guide diagnostic and therapeutic interventions (INVUS). Due to possible serious INVUS complications, structured training concepts are required. Phantoms can facilitate teaching, but their use is currently restricted by complex manufacturing and short durability of the materials. Hence, the aim of this study was the development and evaluation of an optimized abdominal INVUS phantom.Materials and Methods Phantom requirements were defined in a structured research process: Skin-like surface texture, homogeneous matrix with realistic tissue properties, implementation of lesions and abscess cavities in different sizes and depths as well as a modular production process allowing for customized layouts. The phantom prototypes were evaluated in certified ultrasound courses.Results In accordance with the defined specifications, a new type of matrix was developed and cast in multiple layers including different target materials. The phantom structure is based on features of liver anatomy and includes solid focal lesions, vessels, and abscess formations. For a realistic biopsy procedure, ultrasound-proof material was additionally included to imitate bone. The evaluation was performed by US novices (n=40) and experienced participants (n=41). The majority (73/81) confirmed realistic visualization of the lesions. The 3D impression was rated as “very good” in 64% of cases (52/81) and good in 31% (25/81). Overall, 86% (70/81) of the participants certified high clinical relevance of the phantom.Conclusion The presented INVUS phantom concept allows standardized and realistic training for interventions.
Keywords: ultrasound training; free hand puncture; ultrasound-guided interventions; ultrasound-guided biopsy; ultrasound phantom